Donor impurity states in a GaAs square tangent quantum dot. (July 2015) - Zhang, Zhongmin; Guo, Kangxian; Mou, Sen; Xiao, Bo; Zhou, Yingchu
Highlights: A GaAs square tangent quantum dot with hydrogenic impurity have been proposed. The impurity binding energy is obtained by solving Schrödinger equation using variational method. The impurity binding energy is strongly affected by d, U 0, the impurity position and pressure. Abstract: Based on the effective-mass approximation, the impurity binding energy in a square tangent quantum dot is calculated variationally. The impurity binding energy has been calculated as a function of d, U 0, pressure and the impurity position. It is found that d, U 0, pressure and the impurity position have great effects on the impurity binding energy. It is worth to note that the effect of pressure should be taken into consideration in the experimental study of semiconductor nanostructures.